(untitled) (Nigerian Journal of Physiological Sciences, 2022)
Toxic metals such as lead (Pb) cause severe liver damage in humans and animals, with oxidative stress prominently implicated in the pathogenesis of lead acetate‑induced liver injury. Azadirachta indica is hepatoprotective due to its antioxidative effect. This study investigated the antioxidative role of A. indica (AI) and its chemopreventive effect on lead acetate (LA)-induced hepatocellular dysfunction with seventy adult male rats classified into group A- Control (distilled water), group B 0.1% LA only, group C and D- 0.1% LA + 100 mg/kg and 0.1% LA + 200 mg/kg AI respectively, group E- 0.2% LA, group F and G- 0.2% LA + 100 mg/kg and 0.2% LA + 200 mg/kg AI. Oxidative stress markers (MDA and H2O2), antioxidant parameters (GSH, SOD, CAT, GPx, GST), inflammatory markers (MPO and NO), alanine aminotransferase (ALT) and histopathological studies of the liver were evaluated. The results showed that LA administration caused a decrease in GSH, GPx, and GST while AI co-administration increased the activities of the antioxidants. Moreover, LA administration increased MPO, NO, MDA, and H2O2 levels whereas AI significantly reduced (P<0.05) these parameters. Histopathological examination revealed necrosis and mild infiltration by inflammatory cells in LA administered rats, whereas these lesions were absent in AI administered rats. In conclusion, A. indica demonstrates a protective role in lead acetate-induced hepatotoxicity, mainly via oxidative stress inhibition.